FILOSOFIA POLITICA, REPUBLICA Y EDUCACION DEL CIUDADANO - Riba, Jordi (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
This paper intends to analyse how the principles that the Enlightenment considered essential for the individual autonomy materialized, for the first time, in an educational policy, whose aim was the moral and civic formation of the citizen. This policy, initiated by Jules Ferry, during The Third French Republic, was carried out according to two axis: the action of the national teachers and the use of different manuals, whose lecture allows us to discover not only the taught values, but also the adopted procedures to achieve the objectives.